Governance structures and mechanisms of Agroecological Living Landscapes in five countries - Navarrete Cruz, Angela; ElDidi, Hagar; Piraux, Marc; Fuchs, Lisa Elena; Tristan, Maria Claudia; Matangi, Dorcas; Chimonyo, Vimbayi; Alary, Veronique; Idoudi, Zied; Frija, Aymen; Triomphe, Bernard; Bergamini, Nadia (2024)
The CGIAR Initative on Agroecology established Agroecological Living Landscapes (ALLs) in eight countries to foster the development of the context-specific application of the 13 agroecological principles. This document examines the internal governance structures, mechanisms, and organization of six ALLs located in five of those countries, namely, Zimbabwe, Peru, Tunisia, Kenya, and Senegal. Structures refer to the positions of the different actors in decision-making processes specified in governance roles and, in some cases, in internally created 0rganizations (e.g., committees). Mechanisms refer to the rules that (i) regulate coordination between at least two stakeholders, and (ii) allow participation in decision-making within the ALL. A qualitative study was conducted to analyze the structures and mechanisms of the six ALLs. The six ALLs were characterized under four types, following a combination of three types of governance structures (centralized, polycentric, and hybrid), three types of governance mechanisms (formal, informal, and composite), and three types of governance organizations (community-based, host organizations, and multilevel). The ALLs in Zimbabwe are centralized, formal, and community-based with strong synergies between farmer groups, traditional authorities, and local government agencies for agriculture, natural resource management, and social inclusion. The ALL in Peru is polycentric and composite. It consists of strategic networks organized around specific innovations with the engagement of multiple stakeholders that influence public policy. The ALLs in Tunisia and Kenya are hybrid and composite based on host organizations to engage farmers and/or multiple food system actors (FSAs) at the local level. Each of these ALLs is also connected to a multi-stakeholder platform at the regional and/or national level for advocacy and influence on public policy design. Finally, the ALL in Senegal is centralized and formal. It consists of multi-level platforms with internal organizations for coordination, deliberation, and advocacy integrating a wide range of stakeholders at the local, regional, and national levels.